Mobile-assisted learning and higher-education ESP: English for physiotherapy - Pettersson, Lin Elinor (Lingua Posnaniensis, 2018)
The popularity of Mobile-assisted language learning has increased significantly in recent years, and language teachers are still exploring different ways of introducing new technology into the language classroom. Up to the moment, this has mainly been achieved through the use of mobile language-learning applications (Grimshaw et al. 2017). We wanted to push the use of applications in the classroom of English for Specific Purposes further by introducing a human anatomy application in the context of English for physiotherapy in higher education. We believe that the use of an application for a specific area provides the opportunity to enrich the learning experience and take language-learning outcomes to a different level as students are granted a unique occasion of applying knowledge acquired in a specialist area in the language classroom. An intervention proposal was designed for the subject English for physiotherapy (University of Málaga, Spain) bringing together mobile-assisted language learning with a task-based approach to suit constructivist learning processes and accommodate different learning styles and rhythms. We followed five guiding principles on mobile-assisted language learning (Stockwell & Hubbard 2013) to design three tasks for autonomous and collaborative learning using the application 3D4 Medical Essential Anatomy. A preliminary survey was carried out using Lime Survey to measure under-graduate physiotherapy students’ attitudes towards the use of a human anatomy application to learn English and to predict possible challenges (language, technology, cost or storage capacity). The results support our belief as the obtained data indicates that students perceived the use of a human anatomy application as an interdisciplinary tool for both educational and professional purposes and were willing to purchase an application to learn English for physiotherapy.
Keywords: Inglés - Estudio y enseñanza - Innovaciones tecnológicas; MALL; 3D applications; English for Physiotherapy; English for Specific Purposes; 3D4Medical; Task-based language learning; Mobile-Assisted Language Learning